Biodegradation of Polycyclic Aromatic Hydrocarbons by Microbial Consortium: A Distinctive Approach for Decontamination of Soil. Issue 6 (17th August 2016) - Gupta, Gauri; Kumar, Vipin; Pal, Asim Kumar
ABSTRACT: The presence of polycyclic aromatic hydrocarbons (PAHs) in the soil is a major cause of concern due to their toxic nature and ubiquitous occurrence. As PAHs are hydrophobic substances, their solubility in water is very low. This makes them unfit for natural degradation. However, it has been found that several microorganisms have the capability to efficiently degrade soil-sorbed PAHs using different metabolic pathways. As the microbial degradation process is quite economical and does not cause ecological damage, it has been a subject of extensive research for the past several decades. In numerous studies, it has been found that a consortium of microbes is more effective than the individual microbial isolates. The process remains affected by different environmental factors. Therefore, in this article, the current status of the work done on various aspects of biodegradation of ecologically toxic PAHs using different microbial consortia has been reviewed along with the biological aspects of biosurfactants produced during the process. The role of recent technologies such as the next-generation sequencing using omics techniques, metagenomics and metatranscriptomics, has also been discussed. These technologies are critical in understanding the application of microbial consortium, including its potential for future bioremediation in microbial ecology.